Investigation of antioxidant properties of Withania somnifera (L.) Dunal and influence of physico-chemical properties of soil along the topographic gradients in sub-tropical region of the Indian Himalaya - Kundra R,; S S Samant,; SK Nandi,; RK Sharma, (International Journal of Phytomedicine, 2017)
A high value medicinal plant W. somnifera L. Indian Ginseng; Ashwagandha investigated for the antioxidant and influence of physico-chemical properties of soil on antioxidant along the topographical gradients in Kullu Valley, North Western Indian Himalaya. Total phenolic and flavonoid contents in methanol extracts of fruits, leaves, stems and roots were quantified and their antioxidant activities were evaluated using the in-vitro assays such as DPPH, ABTS and FRAP. The study revealed that fruits, leaves, stems and roots of W. somnifera were potent source of natural phenolics and flavonoids and possesses antioxidant activities, which were significantly affected by the changes in altitude (p ≤0.05). Total phenolic and flavonoid contents in different parts of W. somnifera showed significant correlations with soil properties. The study conclude that changes in topographical gradients particularly altitude influenced antioxidant activities of W. somnifera and suggest that antioxidant rich population of a desired medicinal plant should be identified for their conservation management and sustainable utilization in pharmaceutical and food industries.